Comparing Antibiotic Pastes with Electrospun Nanofibers as Modern Drug Delivery Systems for Regenerative Endodontics - Brimo, Nura; Serdaroğlu, Dilek Çökeliler; Uysal, Busra (Current Drug Delivery, 2022)
Nanomaterials can be applied in different biomedical applications like diagnosis, treatment, and drug delivery due to their unique features. Using such materials in the endodontic treatment processes may prove challenging as these materials must exhibit antibacterial effects without posing any harm to the host cells. The approach involving nanofibers loaded with various antibacterial drugs offers a potential treatment method to enhance the elimination procedure of intracanal biofilms. Clinically, many models of bacterial biofilms were prepared under in vitro conditions for different aims. The process of drug delivery from polymeric nanofibers is based on the principle that the releasing ratio of drug molecules increases due to the increase in the surface area of the hosted structure. Our review discusses diverse approaches to loading/releasing drugs on/from nanofibers; we summarized many studies on electrospun nanofibers loaded with various drugs applied in the endodontic field. Moreover, we discussed both the advantages and the limitations of these modern endodontic treatment materials, comparing them with the traditional ones.
Keywords: electrospinning